TEACHER’S RULES IN MANAGING STUDENTS’ MISBEHAVIOR AT JUNIOR HIGH SCHOOL IN PADANG - Rima Nofrianti; Hevriani Sevrika; Armilia Riza (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
In this research, the researcher has some purposes. First, the researcher wants to analyze the kinds of students' misbehavior found in English class. Second, the researcher wants to know the teachers' rules for the student's misbehavior. The data of this research will collect through the observation checklist and interview. The researcher analyzed six kinds of  students’ misbehavior, namely not paying  attention to the teacher while teaching, chatting  with friends during the learning process in  class, sleep when the teacher explains the  material, not doing the assignments given by  the teacher, late for class when teachers  have started the lesson, and does not record lessons given by the teacher. Then the researcher found five teachers' rules for students' misbehavior in the english class yaitu when the bell rings students enter the classroom, if students leave they are only allowed one at a time, students are prohibited from sleeping during class hours, take turns reading the qur'an 1 to 4 students, and no eating in class